Neuromuscular Mimics of Entrapment Neuropathies of Upper Extremities - Gilchrist, James M. (Hand (N Y), 2020)
Introduction: Carpal tunnel syndrome and ulnar neuropathy are such common maladies affecting the upper extremties that they often become the default diagnosis when patients complain of numbness, pain, or weakness of the hands. While often correct, there are a number of other conditions that can also cause sensory or motor loss of the hands, which should be considered when appropriate, as they can mimic upper extremity entrapment syndromes. Methods: In this review, we will discuss such mimics, including Charcot-Marie-Tooth disease, multifocal motor neuropathy, hereditary neuropathy with pressure palsies, mononeuropathy multiplex, Lewis-Sumner syndrome, brachial plexitis (Parsonage-Turner syndrome), myotonic dystrophy, inclusion body myopathy, and distal myopathy of Welander. We will discuss the clinical presentation, as well as diagnostic testing, treatment (if available), and prognosis. Conclusion: The objective is to provide a differential diagnosis for those patients who do not fit well clinically or respond to usual therapy for entrapment neuropathy of the upper extremities.